THE EFFECT OF SCIENCE, ENVIRONMENT, TECHNOLOGY, AND SOCIETY (SETS) APPROACH ASSISTED BY VISUAL MEDIA ON CRITICAL THINKING ABILITY AND STUDENTS' SCIENTIFIC ATTITUDES IN THE MATERIAL OF LIVING CREATOR CLASSIFICATION - Maya Astuti; Binari Manurung; Juriani Juriani (UNIVERSITAS NEGERI MEDAN, 2019)
This study aims to determine the effect of the Science, Environment, Technology, and Society (SETS) approach assisted by visual media on critical thinking abilities and scientific attitudes of students on biology subjects on the classification of living things. The research method used a quasi-experimental research sample of 2 classes determined by random sampling. Class VII1 as many as 32 students were taught with the approach of Science, Environment, Technology, and Society (SETS) assisted by visual media and class VII2 as many as 32 students were taught with conventional learning. The research instrument tests the form of critical thinking Cornell X which is based on Ennis and was independently developed by researchers and scientific attitude observation sheets. The data analysis technique used partial hypothesis testing at a significant level ∝ = 0.05. The results showed 1) There was a significant influence of the approach of Science, Environment, Technology, and Society (SETS) assisted by visual media on students' critical thinking skills (tcount = 2.37; ttable (0.05.62) = 1.66). 2) There is a significant influence of the Science, Environment, Technology, and Society (SETS) approach assisted by visual media on scientific attitudes (tcount = 3.88; table (0.05.62) = 1.66). The results showed that the level of thinking ability using the SETS approach assisted by visual media ((X) ̅ = 82.38) was higher than conventional learning ((X) 49 = 49.00). The results of the study also showed better scientific attitudes in the classroom the SETS approach assisted by visual media ((X) ̅ = 74.63) is better than conventional learning ((X) ̅ = 43.02). Thus, learning science with the SETS approach must continue to be developed because implementing SETS learning can improve students' critical thinking skills and scientific attitudes. Keywords: guided inquiry, dynamic fluid, learning outcomes